Sargassum Enrichment in Mesoscale Eddies of the Great Atlantic Sargassum Belt - Yingjun Zhang; Brian B. Barnes; Dennis J. McGillicuddy Jr.; Chuanmin Hu (Geophysical Research Letters)
Abstract Pelagic Sargassum has increased dramatically in the past decade, primarily in the annually recurrent Great Atlantic Sargassum Belt (GASB) that extends from the coast of West Africa to the Gulf of Mexico. Using satellite observations of Sargassum density and mesoscale eddies from 2011 to 2023, we investigate whether more Sargassum can be found in mesoscale eddies. Cyclonic eddies were found to contain 6%–47% more Sargassum (relative to eddy‐free waters) across all selected regions within the GASB, with the highest Sargassum density in their inner cores (<0.5 eddy radius). Impacts of anticyclonic eddies were weaker and varied between regions. In addition, Sargassum enrichment tended to be higher in eddies with greater size or amplitude, such as the North Brazil Current rings and those in the Caribbean Sea. These findings may inform Sargassum mitigation strategies, for example, through physical removal in targeted locations.